Characterizing the microstructure of deteriorated cementitious materials with x-ray microtomography. - Promentilla, Michael Angelo B. (Asean Engineering Journal)
Cementitious material such as concrete is not only the most widely used infrastructure material, but it is also now being considered as an engineered barrier material for nuclear waste repository due to its structural strength and high confinement capacity for a long period of time. It is therefore imperative to understand how microstructure changes during deterioration to assess its long-term durability performance. This paper presents some applications of X-ray microtomography to examine the microstructure of deteriorated cementitious materials. X-ray microtomography is becoming an attractive option for nondestructive and noninvasive three-dimensional (3D) imaging of internal structure of materials. As this technique operates on the same basic principle of medical CT (Computed tomography) scanners, it provides the 3D reconstruction of images from finite radiological images; but with much higher spatial resolution. For example, a microfocus X-ray CT system was used in our study to visualize the connected crack network of frost-induced damaged mortar at spatial resolution of orders of 10 um. Moreover, synchrotron-based microtomography was also used to visualize at submicron level the pore spaces of mortar being deteriorated due to calcium leaching. Not only the CT images provide the qualitative information, but also these images allow us to make quantitative measurement of 3D parameters such as the connectivity and tortuosity. Representative samples from the analyzed 3D images were presented to demonstrate the microtomography in understanding the relationship between the microstructure and durability performance of these cementitious materials.